Post-operative antibiotics for cutaneous abscess after incision and drainage: Variations in clinical practice - El Boghdady Michael; Ewalds-Kvist Beatrice Marianne; Zhao Sarah; Najdawi Ahmad; Laliotis Aggelos (Microbiology Society, 2022)
Background.
Acute cutaneous abscess is a common surgical condition that mostly requires incision and drainage. Despite this, there is no standardized national or international guidance on post-operative antibiotics prescription. Traditionally, antibiotics are not indicated unless complications and/or risk factors such as immunocompromisation, diabetes or cellulitis exist. We aimed to study the local practice for post-operative antibiotics prescription for cutaneous abscesses in a UK university teaching hospital.
Methods.
Retrospective data collection for emergency general surgical admissions for a period of 6 months was carried out. All patients with cutaneous abscesses were included in this analysis. Scrotal, breast and limb abscesses were excluded. Patients’ demographics, co-morbidities and complications, including local (cellulitis, necrosis) and systemic (e.g sepsis), were studied. Approval for access to patient data was granted by the local clinical governance department prior to the commencement of this study. Computations were performed using IBM SPSS version 26. Chi square (X2), Pearson correlation (r), one or two samples t-test (one or two tailed) were applied.
Results.
A total of 148 patients were included. The mean age was 40 years (55 % males). The most common site of abscess was perianal (27.7 %), followed by pilonidal (20.3 %) and axilla (16.9 %). A total of 107 (73 %) were managed surgically with incision and drainage, and of these 92 (86 %) were managed within 24 h. Altogether, 83 (76 %) were prescribed post-operative antibiotics, while only 25 (23 %) had indications. The most used post-operative empirical antibiotics was co-amoxiclav (59 %). There was a significant relationship between ‘abscess site’ × ‘antibiotics’ [X2 (36)=54.8, P=0.023]. A total of 103 patients’ average duration of post-operative antibiotics was 7.2 (sd 2.9) days. Ten patients subject to readmission spent an average of 8.4 (sd 3.8) days on antibiotics.
Conclusions.
There were variations in clinical practice regarding post-operative antibiotic prescription for cutaneous abscesses. Research is required in the future in cooperation with microbiologists to develop a standardized evidence-based treatment protocol for the management of such a common surgical condition.